(untitled) (Journal of Health, Population and Nutrition, 2013)
This article attempts to highlight the prevalence of zinc deficiency and its health and economic consequences in South Asian developing countries and to shed light on possible approaches to combating zinc deficiency. A computer-based search was performed on PubMed, Google, and ScienceDirect.com to retrieve relevant scientific literature published between 2000 and 2012. The search yielded 194 articles, of which 71 were culled. Studies were further screened on the basis of population groups, age and sex, pregnancy, and lactation. The most relevant articles were included in the review. Cutoffs for serum zinc concentration defined for zinc deficiency were 65 ?g/dL for males and females aged <10 years, 66 ?g/dL for non-pregnant females, and 70 ?g/dL for males aged ?10 years. Population segments from rural and urban areas of South Asian developing countries were included in the analysis. They comprised pregnant and lactating women, preschool and school children. The analysis reveals that zinc deficiency is high among children, pregnant and lactating women in India, Pakistan, Bangladesh, Sri Lanka, and Nepal. Diarrhoea has been established as a leading cause to intensify zinc deficiency in Bangladesh. Little has been done in Sri Lanka and Nepal to estimate the prevalence of zinc deficiency precisely. A substantial population segment of the South Asian developing countries is predisposed to zinc deficiency which is further provoked by increased requirements for zinc under certain physiological conditions. Supplementation, fortification, and dietary diversification are the most viable strategies to enhancing zinc status among various population groups. J HEALTH POPUL NUTR 2013 Jun; 31(2): 139-149 DOI: http://dx.doi.org/10.3329/jhpn.v31i2.16378